Preparation and application method of a high-performance boron-free prefabricated board
By using boron -free active agents and liquid sintering technology, the problem of cracks and performance decline in traditional high -temperature alloy repair methods is solved, and high -efficiency and excellent performance repair effects are achieved.
Patent Information
- Application Number
- CN202211694250.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-28
AI Technical Summary
In the existing high-temperature alloy repair technology, traditional fusion welding and brazing methods are prone to cause cracks and performance degradation, while powder metallurgy repair affects the binding strength and high-temperature performance due to the precipitation of borides.
The boron -free active agent is used to avoid the precipitation of the boronicides by adjusting the proportion of the element ingredients and achieve efficient repair through liquid sintering technology. The main composition element of the boron -free activator is basically the same as the high -temperature alloy body. Only through element regulation to ensure that the tissue density and performance in the repair area are excellent.
The efficiency and performance of high -temperature alloy restoration are achieved, and the problems of decline in cracks and performance are avoided, while at the same time ensure the tightness and strengthening mechanism of the tissue of the repair area.
Smart Images

Figure CN116083771B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material engineering, and specifically relates to a preparation and application method of a high-performance boron-free prefabricated plate. Background Art
[0002] High-temperature alloys are key materials for gas turbine manufacturing. They are usually nickel-based high-temperature alloys with high Al and Ti contents. The volume percentage of γ' (Ni3Al phase) is generally as high as 60% or more. This type of material has high high-temperature strength and poor weldability. Traditional high-temperature alloy repair methods are mainly divided into fusion welding and brazing. When repairing high-aluminum-titanium alloys with fusion welding, it is difficult to avoid the precipitation of γ' during the welding melting process. , Phase, under the action of welding stress, crystal cracks are formed. The possibility of microcracks is proportional to the amount of γ' (Ni3Al phase), and the strength, oxidation resistance and corrosion resistance of the repaired area are also significantly reduced. Vacuum brazing belongs to overall heating, which reduces the probability of cracks, and is prone to problems such as linear low-melting eutectics, large borides, and component segregation, which seriously affect the bonding strength and high-temperature performance. Powder metallurgy repair and remanufacturing makes up for the shortcomings of cladding welding and brazing. Most powder metallurgy activators use boron as a melting point inhibition element, which has good diffusion performance and melting point inhibition. At the same time, hard and brittle borides or low-melting eutectics are formed in the repair area. During the heat treatment process, the eutectic melts to form hole defects, and the long-term diffusion of the eutectic phase will destroy the substrate structure. For this reason, the boron-free activator whose composition design takes into account both melting point inhibition and parent material matching is the most ideal type of activator at this stage.
[0003] High-temperature alloy blades work in harsh environments such as high temperature, high pressure, and corrosive gas for a long time, and are prone to defects such as coarse cracks and corrosion pits. After removing the defects, the area to be repaired generally presents narrow deep grooves and large areas of lack of meat. Therefore, designing a boron-free activator with excellent melting point inhibition is particularly important for good flow filling. At the same time, due to the difficulty in the preparation process of boron-free activator powder, especially the high content of melting-reducing elements Ti, Al, Ta, and Nb and their easy oxidation, the traditional method of powder mixing, due to the large specific surface area, incomplete metallurgical bonding under vacuum conditions, poses a challenge to the processability of the boron-free activator. Summary of the invention
[0004] The purpose of the present invention is to provide a boron-free activator to solve the problems in the prior art. The main constituent elements of the boron-free activator are basically the same as those of the high-temperature alloy body, without external elements, and only through element regulation, boron is avoided as a melting point suppression or melting point control element, and large-scale precipitation of borides is avoided. It can be used to repair alloys with good oxidation resistance, creep performance and high strength such as Mar-MARM247 or IN738LC, and can also be used for other nickel-based high-temperature alloys.
[0005] Another object of the present invention is to provide a method for repairing high-temperature alloy parts by liquid phase sintering molding using the above-mentioned boron-free activator.
[0006] The third object of the present invention is to provide a method for preparing a high-performance boron-free prefabricated board using the above-mentioned boron-free activator.
[0007] In order to achieve the above invention object, the technical solution of the present invention is:
[0008] A boron-free activator comprises an activator powder, wherein the activator powder comprises the following elements in percentage by weight: 14.0 to 18.0% Cr, 5.0 to 7.0% Al, 5.0 to 7.0% Ti, 8.0 to 12.0% Co, 1.5 to 6.0% Nb, 9.0 to 12.0% Mo, 3.0 to 7.0% Ta, 0.01 to 0.1% W, 0.05 to 0.10% Zr, and the remainder is nickel and unavoidable impurities, and the total percentage content is 100%.
[0009] As a preferred embodiment of the present application, the melting point of the boron-free activator is 1140°C to 1170°C.
[0010] The boron-free activator composition does not contain traditional melting point depressing elements such as boron, silicon, zirconium, hafnium, etc., which are all strengthening elements in high-temperature alloys and do not produce heterogeneous weakening phases; the alloy melting point inhibition effect is good; and there are two preparation methods: direct sintering and pre-set plate.
[0011] A method for repairing a high-temperature alloy component by liquid phase sintering molding using the boron-free activator comprises the following steps:
[0012] Step 1 Preparation of boron-free activator powder
[0013] Select Ni, Co, Ta, W, Cr, Ti, Al, Nb, Mo, and Zr with a purity of not less than 99.99%, and mix them according to the proportion; melt the above raw materials into alloy ingots by a vacuum induction melting furnace; prepare them into powder by rotating electrodes or vacuum atomization for standby use;
[0014] Step 2: Blank preparation
[0015] Preparation of base powder blank: nickel-based high-temperature alloy powder is used as base powder (base powder is commercially available high-temperature alloy powder, such as MarM247 or IN738LC, etc.), a binder is added thereto and stirred evenly, and the mixed blank powder is evenly coated on the defect to be repaired and set aside;
[0016] Preparation of boron-free activator slurry: Add a binder to the boron-free activator powder prepared in step 1 and stir evenly for standby use;
[0017] Preparation of composite blank: evenly apply the slurry prepared with boron-free activator powder on the base material powder blank, dry it naturally for 8-24 hours, and then set it aside;
[0018] Step 3 Vacuum liquid phase sintering
[0019] The composite blank is placed in a vacuum heat treatment furnace for transient liquid phase sintering, and then cooled in the furnace.
[0020] Step 4: Resize
[0021] Machine or grind the repaired area to restore the dimensional profile.
[0022] As a preferred embodiment of the present application, in step 1, the boron-free activator powder is sieved to obtain a powder particle size of 5 to 106 microns.
[0023] As a better implementation method in the present application, in step 2, when preparing the base material powder blank, the amount of the binder added is 0.5%-0.8% of the base material powder; when preparing the boron-free activator slurry, the amount of the binder added is 0.8%-1.2% of the boron-free activator powder; when preparing the composite blank, the mass ratio of the base material powder blank to the boron-free activator powder slurry is 1:0.5-1.3 (the two additions here, one is the base material powder plus the binder to form the blank, and the other is the activator plus the binder placed on the blank, and the two additions have a certain proportional relationship), and the slurry prepared by the boron-free activator powder is evenly coated on the base material powder blank and must be naturally dried for 8-24 hours.
[0024] The above-mentioned adhesive is a commercial product, preferably NICROBRAZ-S adhesive from Wall Colmonoy Corporation.
[0025] As a preferred embodiment of the present application, the conditions for vacuum liquid phase sintering in step 3 are: the vacuum degree of the vacuum furnace is 1.0×10 -2 Pa, heat up to 1180℃±5℃-1220℃±5℃ at a rate of 5℃-15℃ / min, and keep warm for 30min-120min.
[0026] A method for preparing a boron-free prefabricated welding plate for high-temperature alloy repair using the above-mentioned boron-free activator comprises the following steps:
[0027] Step 1 Preparation of boron-free activator powder
[0028] Select Ni, Co, Ta, W, Cr, Ti, Al, Nb, Mo, and Zr with a purity of not less than 99.99%, and mix them according to the proportion; melt the above raw materials into alloy ingots by a vacuum induction melting furnace; prepare them into powder by rotating electrodes or vacuum atomization for standby use;
[0029] Step 2 Preparation of prefabricated welding slab
[0030] Preparation of base material powder slab: nickel-based high temperature alloy powder is used as base material powder (base material powder is commercially available high temperature alloy powder, such as MarM247 or IN738LC, etc.), a binder is added thereto and stirred evenly, the mixed base material powder is piled on a high temperature alloy plate or a ceramic plate into a slab of 1 to 10 mm, and a fixed height mold is used for leveling;
[0031] Preparation of boron-free activator slurry: Add a binder to the boron-free activator powder prepared in step 1 and stir evenly for standby use;
[0032] Preparation of composite blank: evenly apply the slurry prepared by boron-free activator powder on the base material powder blank, dry naturally and pre-sinter in a vacuum furnace, and then cool with the furnace or air cool;
[0033] Step 3: Prefabricated welding plate finalization
[0034] According to the visual inspection results of the blank, the loose boundaries and rough surfaces are ground by grinding to reveal the complete metallic luster; the removed boundaries and surfaces should include areas with loose holes and severe segregation;
[0035] Step 4: Cleaning / Storage
[0036] Clean the surface of the prefabricated board with acetone solution by ultrasonic wave, dry it and seal it in vacuum for later use;
[0037] Step 5: Assembly
[0038] Grind the area to be repaired flat, and according to the size of the defect to be repaired, process the required shape on the prefabricated welding plate and assemble and place it on the defect to be repaired. The top view assembly can be placed directly; the side assembly needs to be clamped or spot welded;
[0039] Step 6 Repair
[0040] Liquid phase sintering is carried out in a vacuum heat treatment furnace, and then cooled with the furnace after completion;
[0041] Step 7 Size Restoration
[0042] Machine or grind the repaired area to restore the dimensional profile.
[0043] As a better implementation method in the present application, in step 2, the particle size of the base material powder is 53-106μm; the particle size of the boron-free activator powder is 5-106 microns; when preparing the base material powder slab, the added binder is 0.5%-0.8% of the base material powder; when preparing the boron-free activator slurry, the added binder is 0.8%-1.2% of the boron-free activator powder; when preparing the composite blank, the mass ratio of the base material powder to the boron-free activator is 1:0.5-1.3, and the natural drying time is 8-24h; the conditions for vacuum pre-firing are: the vacuum degree is 1.0×10-3Pa, the temperature is increased to 1160℃±5℃-1180℃±5℃ at a rate of 5℃-15℃ / min, and the temperature is kept for 5min-30min.
[0044] As a better implementation method in the present application, in the step six repair step, the conditions of vacuum heat treatment are: vacuum degree 1.0×10-3Pa, heating to 1190℃±5℃-1220℃±5℃ at a rate of 5℃-15℃ / min, and keeping warm for 30min-120min.
[0045] The present application also protects a boron-free prefabricated welding plate prepared by the aforementioned method.
[0046] The prefabricated plate is prepared by layering plastic powder, and the temperature is kept slightly higher than that of the boron-free activator. The liquid and solid phases are separated, and the brazing material enters the gap between the base material powders under the action of capillary force, ensuring that the boron-free activator is evenly distributed and the amount is minimized. The solid oxide is retained in the surface residue and removed by grinding. At the same time, the metallurgical bonding of the welding area is good.
[0047] The prefabricated plate is prepared by pre-sintering, and the parent material and the boron-free activator are mixed to prepare a "high-temperature metastable" plate with a certain strength, which has good processing performance. At the same time, a certain amount of active diffusion elements are preserved, and the plate has stable remelting and welding performance during sintering; the activator is filled in the liquid phase, which is very adaptable to the solid-liquid phase transition during the sintering process, avoiding the holes caused by the liquid-solid phase volume transition; one more pre-sintering and solidification, the volume shrinkage after welding is very small, effectively avoiding the generation of microcracks, and is particularly suitable for the repair of three-dimensional structures with high shrinkage requirements.
[0048] The quality of the prefabricated board determines the sintering quality. By checking the organizational structure of the prefabricated parts, the quality of the repair can be monitored, solving the problem of being unable to destroy and inspect after repair.
[0049] The aforementioned main scheme of the present invention and its further options can be freely combined to form multiple schemes, all of which are schemes that can be adopted and claimed for protection by the present invention; and in the present invention, (non-conflicting options) options and other options can also be freely combined. After understanding the scheme of the present invention, those skilled in the art can understand that there are many combinations based on the prior art and common knowledge, all of which are technical schemes to be protected by the present invention, and they are not exhaustively listed here.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The boron-free activator in the present invention is a Ni-Co-Ta-W-Cr-Ti-Al-Nb-Mo-Zr high-temperature alloy boron-free activator, which can be used to repair alloys with good oxidation resistance, creep performance and high strength such as Mar-MARM247 or IN738LC, and can also be used for other nickel-based high-temperature alloys;
[0052] (ii) The main components of the boron-free activator are basically the same as those of the high-temperature alloy body, without any external elements, and only by adjusting the proportion of the elements; avoiding the use of boron as a melting point suppression or melting point control element, and avoiding the large-scale precipitation of borides; the content of the boron-free activator can be adjusted according to the morphological characteristics of the substrate, alloy powder and the area to be repaired to achieve the most suitable ratio;
[0053] (III) The repair material of the present invention can be used for powder metallurgy, brazing, large gap brazing, and prefabricated plate welding repair. The elements of the boron-free activator are consistent with the elements contained in the nickel-based high-temperature alloy, and a metallurgical bonding connection is obtained without affecting the phase structure of the substrate. The repair material with the composition characteristics of the present invention can be a powder, a sheet, a plate or a foil strip;
[0054] (iv) The blank of the present invention can be prepared at the repair position and directly sintered and formed for repair without pre-firing;
[0055] (V) Prefabricated panels have high density and good machining performance; by cleaning the oil stains, the inherent melting and welding performance can be guaranteed. Using prefabricated panels for welding repairs, one more pre-burning, less solidification shrinkage during welding repairs, less prone to cracks, and good thermal shock resistance. The repair process can be combined with the heat treatment process;
[0056] (VI) The boron-free activator is fully and evenly mixed with the base material powder by filling the gaps between the base material powders; the proportion of the boron-free activator can be adjusted within a certain range by adjusting the particle size ratio of the master alloy powder; during the preparation of the prefabricated board, the boron-free activator flows into the gaps between the base material powders, with a small amount, uniform tissue composition, and less hard and brittle heterogeneity; because it is liquid phase filling, the volume change caused by the liquid-solid conversion process during the subsequent repair process when it is melted again is avoided, and the generation of holes or cracks is suppressed;
[0057] (VII) Brazing and powder metallurgy repairs cannot accept destructive sampling, and mainly rely on strict process control and non-destructive testing to ensure the quality of repair. This method can accurately infer the quality of repair after sintering by checking the metallographic structure and porosity of the prefabricated plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1The metallographic microstructure of the boron-free prefabricated welding plate prepared in Example 11 of the present invention is
[0059] Figure 2 Schematic diagram of thickening application of nickel-based high-temperature alloy substrate in Example 13
[0060] Figure 3 The microstructure morphology of the MarMARM247 nickel-based high-temperature alloy substrate after thickening and repair in Example 13
[0061] Figure 4 The microstructure morphology of the IN738LC nickel-based high-temperature alloy substrate after thickening and repair in Example 13
[0062] Figure 5 Schematic diagram of the repair of the narrow deep groove recorded in Example 12
[0063] Figure 6 This is the microstructure morphology of the narrow deep groove repaired in Example 12
[0064] Figure 7 Schematic diagram of butt welding in Example 14
[0065] Figure 8 These are the mechanical property test results of the boron-free prefabricated welding plate in Example 14.
[0066] Fig. 9 The inventor used a boron-containing activator to repair the effect diagram DETAILED DESCRIPTION
[0067] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0068] It should be noted that in order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0069] In addition, the present invention should be pointed out that, in the present invention, unless the specific structure, connection relationship, positional relationship, power source relationship, etc. are specifically written out, the structure, connection relationship, positional relationship, power source relationship, etc. involved in the present invention are all known by those skilled in the art on the basis of the prior art without creative work.
[0070] The adhesives used in the following embodiments are all commercial products, for example, NICROBRAZ-S adhesive from Wall Colmonoy Corporation.
[0071] Embodiment 1-10:
[0072] A boron-free activator comprises an activator powder, wherein the activator powder is a powder comprising the following elements in percentage by mass, as shown in the following table:
[0073]
[0074] The boron-free activator in Examples 1-10 is prepared according to the mass percentage, and the above raw materials are melted into alloy ingots by vacuum induction melting furnace respectively; then the powder is prepared by rotating electrode or vacuum atomization, and the powder particle size is screened to obtain a powder with a particle size distribution of 5 to 106 microns. The obtained powder is tested by DSC, showing that the melting point is between 1140-1170°C. The present invention does not add harmful elements of B, Zr, and Si high-temperature alloys, and only achieves melting point control by adjusting the content of component elements.
[0075] Example 11: Preparation of Boron-free Prefabricated Board
[0076] Step 1: Base material powder slab
[0077] The base material powder is MARM247 nickel-based alloy powder. Add a binder (the addition amount is 0.6% of the base material powder mass) to the base material powder and mix them evenly in a powder mixer; pile the mixed base material powder on a high-temperature alloy plate to form a 5mm slab, flatten it with a fixed height mold, and set it aside.
[0078] Step 2: Boron-free activator slurry
[0079] Add a binder (the amount added is 1% of the mass of the boron-free activator powder) to the boron-free activator powder (prepared according to the ratio tables in Example 9 and Example 10, respectively), and stir evenly in an agate mortar to obtain a boron-free activator slurry for standby use.
[0080] Step 3: Preparation of composite blank
[0081] The slurry prepared by the boron-free activator powder is evenly coated on the base material powder blank plate, and the weight is quantitative, M 母材粉 :M 无硼活化剂=1:1, and then pre-fired in a vacuum furnace after natural drying for 24 hours. The vacuum degree of the vacuum furnace is 1.0×10 -3 Pa, the prepared composite green sheet was heated to 1170℃±5℃ and 1180℃±5℃ at a rate of 15℃ / min, respectively, and kept warm for 30min. After that, it was cooled in the furnace.
[0082] Step 4: Remove excess activator powder.
[0083] Due to the high titanium and aluminum content of boron-free activator powder and the constraints of the preparation process, the mixing method cannot complete the metallurgy; the infiltration method is adopted, the activator is liquefied during sintering, and enters the gaps between the base material powders under the action of capillary force, less solder is introduced, and there is no aggregation of solder powder to cause tissue segregation; the obtained prefabricated board has uniform tissue, no full reaction, obvious particle structure of the base material powder, and the boron-free activator is filled in the gaps between the base material powders; filling with liquid phase can avoid liquid-solid phase conversion again, volume change, cracks or cracking, metallographic diagram; the tissue is dense and can be formed by various machining processes without worrying about pollution such as coolant.
[0084] Embodiment 12: The method for using boron-free activator powder for powder metallurgy repair comprises the following steps:
[0085] Step 1 Blank preparation
[0086] Preparation of base material powder blank: the base material powder is commercial grade IN738LC high temperature alloy powder. Add binder to the base material powder (the addition amount is 0.7% of the base material powder mass), and mix them evenly in a powder mixer; evenly apply the mixed blank powder on the defect to be repaired, 2mm higher than the defect, and set aside.
[0087] Preparation of boron-free activator slurry: Add a binder (the amount added is 0.8% of the mass of the boron-free activator powder) to the boron-free activator powder obtained according to the boron-free activator formula of Example 1, stir evenly in an agate mortar to obtain a boron-free activator slurry for standby use.
[0088] Preparation of composite blank: evenly apply the boron-free activator slurry on the base material powder blank, in the weight ratio of M base material powder: M boron-free activator = 1:1.2, dry naturally for 24 hours and set aside.
[0089] Step 2 Vacuum liquid phase sintering
[0090] Transient liquid phase sintering was carried out in a vacuum heat treatment furnace with a vacuum degree of 1.0×10 -2 Pa, heat up to 1200±5℃ at a rate of 15℃ / min, keep warm for 45min, and cool with the furnace after the insulation.
[0091] Step 3: Size recovery
[0092] Machine or grind the repaired area to restore the dimensional profile.
[0093] Repair effect: Interface: good connection, little damage to the substrate, and the remelting transition area formed is about 10 microns; the weld area has dense structure: dense structure, complete metallurgical bonding, no holes, defects, brittle phases; impurities or oxygen-containing components are retained on the surface of the repair area and are subsequently removed with the residue.
[0094] Example 13: A method for repairing a high-temperature alloy component (thickening repair of MARM247 nickel-based alloy) by liquid phase sintering molding using a boron-free activator, comprising the following steps: (preform repair-surface thickening)
[0095] Step 1: Assembly
[0096] The area to be repaired is polished and smoothed, and according to the size of the defect to be repaired, the prefabricated board prepared by using the activator powder obtained by the activator formula in Example 9 is processed into a required shape and assembled and placed on the defect to be repaired or fixed by spot welding.
[0097] Step 2 Repair
[0098] Micro melting metallurgy repair connection is carried out in a vacuum heat treatment furnace, and the vacuum degree of the vacuum heat treatment furnace is better than 1.0×10 - 3 Pa, heat up to 1200±5℃ at a rate of 15℃ / min, keep warm for 120min, and cool with the furnace after the insulation is completed.
[0099] Step 3: Size recovery
[0100] Machine or grind the repaired area to restore the dimensional profile.
[0101] Embodiment 14:
[0102] A method for preparing a boron-free prefabricated welding plate (nickel-based high alloy butt welding) for high temperature alloy repair using the above-mentioned boron-free activator comprises the following steps: (prefabricated plate repair-butt welding)
[0103] Step 1: Assembly
[0104] The prefabricated plate prepared from the activator powder obtained in Example 10 is clamped between two high-temperature alloy butt surfaces and fixed.
[0105] Step 2 Vacuum liquid phase sintering
[0106] Transient liquid phase sintering is carried out in a vacuum heat treatment furnace with a vacuum degree better than 1.0×10 -3 Pa, heat up to 1200℃±5℃ at a rate of 5℃ / min, keep warm for 45min, and cool with the furnace after the insulation.
[0107] Step 3: Size recovery
[0108] Machine or grind the repaired area to restore the dimensional profile.
[0109] Examples 12-14 are examples of prefabricated plate applications. The use of prefabricated plate repair can make up for the shortcomings of powder metallurgy repair, such as large-area repairs that are prone to shrinkage cracks, through-defects that cannot be coated with powder, and repair cases with size requirements. The prefabricated parts can be destroyed and sampled for metallographic analysis. The use of prefabricated parts for repair can estimate the repair effect based on the metallographic structure of the prefabricated parts; the prefabricated parts have been pre-burned once, and will shrink, deform, or crack when sintered again; the repair strength is equivalent to direct powder metallurgy, reaching more than 90% of the base material. The mechanical properties test results of the boron-free prefabricated welded plate are shown in the table below:
[0110]
[0111] Comparative Example 1: A nickel-based powder metallurgy repair material and its application
[0112]
[0113] The active auxiliary nickel-based high-temperature alloy described in Comparative Example 1 has the same effect as the boron-free activator of the present invention, and has a relatively simple composition. At the same time, the B content is 2-4%, which is a conventional melting point depressing element. This is essentially different from the use of Cr, Mo, Al, Ti, Nb, and Ta as melting point depressing elements in the present invention.
[0114] Boron in boron-containing activators has excellent melting point inhibition, high-temperature fluidity, and fast diffusion rate, but excessive B is harmful to the structure of high-temperature alloys. It is easy to combine and fix the strengthening elements in the matrix, causing the performance of the matrix to deteriorate.
[0115] The repaired structure contains a large amount of low-melting eutectics and brittle borides, and even forms serious segregation due to transition flow, and is easy to melt and form holes during heat treatment; the boron element has extremely strong diffusivity, and also diffuses slowly at the service temperature, consuming the strengthening elements of the substrate; using the boron-free activator of the present invention, the main components are consistent with the substrate, without external elements, the repaired area has a strengthening mechanism and structure consistent with the substrate, the diffusion rate of Cr, Mo, Al, Ti, Nb, and Ta is an order of magnitude different from that of B, and can produce a good transition and connection area. At the same time, the substrate is not excessively damaged, and the structure of the repaired area is similar to the substrate, dense, without eutectic and brittle phases, which is a guarantee of excellent performance.
[0116] Comparative Example 2: Structural brazing repair of super alloy components
[0117]
[0118]
[0119] The present invention is essentially different from Comparative Example 2, that is, the brazing material described in Comparative Example 2 has a higher liquidus temperature, with a liquidus of about 1215°C and a melting temperature range of 5°C, and is mainly used for brazing. It may not be used for nickel-based alloys with a heat treatment temperature below 1215°C. This is because brazing exceeding the solid solution temperature of the alloy itself will bring about the risk of local initial melting of the alloy, especially for large-sized components. This tendency will be further increased due to element segregation; the liquidus of the present invention is around 1160°C, and due to the low brazing temperature, it is applicable to most nickel-based alloys.
[0120] Compared with the brazing material described in Comparative Example 2, the Al content of the present invention is higher, which enhances the oxidation resistance at high temperature and avoids the premature failure of the weld under high temperature oxidation conditions. Adding Nb element and increasing the Ta element content further enhance the strength and creep resistance of the repaired area after powder metallurgy.
[0121] The room temperature tensile strength of the repaired joint of the present invention is equivalent to that of the base material, the 900°C tensile yield strength is higher than that of the base material, and the average tensile strength is slightly lower than that of the base material.
[0122] Comparative Example 3: Low Melting Point Brazing Alloy for High Temperature Applications
[0123]
[0124] The liquidus temperature of the brazing material described in Comparative Example 3 is relatively high, and it is mainly used for capillary brazing. The brazing temperature is 1225°C-1250°C, which is equivalent to or higher than the solution temperature of most nickel-based high-temperature alloys and close to the initial melting temperature. There are risks in its application, especially for the heat treatment of larger parts, which generally adopts a more conservative semi-solution treatment temperature. The liquidus of the present invention is about 1160°C, and it is mainly used for powder metallurgy. Liquid phase reaction sintering can be completed below 1200°C, which is lower than the solution temperature of most nickel-based high-temperature alloys, and has a wider application space.
[0125] The activator described in Comparative Example 3 contains Mn, which is not a strengthening element in high-temperature alloys and is usually limited to an extremely low content in high-temperature alloys.
[0126] The above-mentioned embodiments are only preferred implementations of this patent, but the protection scope of this patent is not limited thereto. It should be pointed out that, for ordinary technicians in this technical field, without departing from the principle of this patent, according to the technical solution and patent concept of this patent, several improvements and modifications can be made, and these improvements and modifications should also be considered within the protection scope of this patent.
Claims
1. A high temperature alloy boron-free activator, comprising an activator powder, characterized in that The activator powder is a powder comprising the following elements in percentage by mass: 14.0-18.0% Cr, 5.5-7.0% Al, 5.5-7.0% Ti, 8.0-12.0% Co, 1.5-4.5% Nb, 9.0-12.0% Mo, 3.0-7.0% Ta, less than 0.01% W, 0.05-0.10% Zr, and the remainder is nickel and unavoidable impurities, and the total percentage content is 100%. The boron-free activator has a melting point of 1140-1170°C. It is used for repairing alloys with good oxidation resistance, creep performance and high strength, or for repairing nickel-based high-temperature alloys.
2. A method for repairing high temperature alloy parts by liquid phase sintering molding using the boron-free activator as claimed in claim 1, characterized in that: The following steps are involved: Step 1 Preparation of boron-free activator powder Select Ni, Co, Ta, W, Cr, Ti, Al, Nb, Mo, and Zr with a purity of not less than 99.99%, and mix them in proportion; melt the above raw materials into alloy ingots through a vacuum induction melting furnace; prepare them into powder through a rotating electrode or vacuum atomization method for standby use; Step 2: Blank preparation Preparation of base material powder blank: nickel-based high temperature alloy powder is used as base material powder, a binder is added thereto and stirred evenly, and the mixed blank powder is evenly coated on the defect to be repaired and set aside; Preparation of boron-free activator slurry: Add a binder to the boron-free activator powder prepared in step 1 and stir evenly for standby use; Preparation of composite blank: evenly apply the slurry prepared with boron-free activator powder on the base material powder blank, dry it naturally for 8-24 hours, and then set it aside; Step 3 Vacuum liquid phase sintering The composite blank is placed in a vacuum heat treatment furnace for instantaneous liquid phase sintering, and then cooled in the furnace after completion; Step 4: Resize Machine or grind the repaired area to restore the dimensional profile.
3. The method according to claim 2, characterized in that: In step 1, the boron-free activator powder is sieved to obtain a powder particle size of 5 to 106 microns.
4. The method according to claim 2, characterized in that: In step 2, when preparing the base material powder blank, the amount of binder added is 0.5%-0.8% of the base material powder; when preparing the boron-free activator slurry, the amount of binder added is 0.8%-1.2% of the boron-free activator powder; when preparing the composite blank, the mass ratio of the base material powder blank to the boron-free activator powder slurry is 1:0.5-1.3, and the slurry prepared with the boron-free activator powder is evenly coated on the base material powder blank and must be naturally dried for 8-24 hours.
5. The method according to claim 2, characterized in that Step 3 Vacuum liquid phase sintering conditions are: vacuum furnace vacuum degree is 1.0×10 -2 Pa, heat up to 1180℃±5℃-1220℃±5℃ at a rate of 5℃-15℃ / min, and keep warm for 30min-120min.
6. A method for preparing a boron-free prefabricated welding plate for high-temperature alloy repair using the boron-free activator according to claim 1, characterized in that The following steps are involved: Step 1 Preparation of boron-free activator powder Select Ni, Co, Ta, W, Cr, Ti, Al, Nb, Mo, and Zr with a purity of not less than 99.99%, and mix them in proportion; melt the above raw materials into alloy ingots through a vacuum induction melting furnace; prepare them into powder through a rotating electrode or vacuum atomization method for standby use; Step 2 Preparation of prefabricated welding slab Preparation of base material powder slab: nickel-based high-temperature alloy powder is used as base material powder, a binder is added thereto and stirred evenly, the mixed base material powder is piled on a high-temperature alloy plate or ceramic plate into a slab of 1-10 mm, and a fixed height mold is used for leveling; Preparation of boron-free activator slurry: Add a binder to the boron-free activator powder prepared in step 1 and stir evenly for standby use; Preparation of composite blank: evenly apply the slurry prepared by boron-free activator powder on the base material powder blank, dry naturally and pre-sinter in a vacuum furnace, and then cool with the furnace or air cool; Step 3: Prefabricated welding plate finalization According to the visual inspection results of the blank, the loose boundaries and rough surfaces are ground by grinding to reveal the complete metallic luster; the removed boundaries and surfaces should include areas with loose holes and severe segregation; Step 4: Cleaning / Storage The surface of the prefabricated board is cleaned by ultrasonic wave with acetone solution, and then vacuum sealed after drying for standby use; Step 5: Assembly Grind the area to be repaired flat, and according to the size of the defect to be repaired, process the required shape on the prefabricated welding plate and assemble and place it on the defect to be repaired. The top view assembly can be placed directly; the side assembly needs to be clamped or spot welded; Step 6 Repair Liquid phase sintering is carried out in a vacuum heat treatment furnace, and then cooled with the furnace after completion; Step 7 Size Restoration Machine or grind the repaired area to restore the dimensional profile.
7. The method according to claim 6, characterized in that In step 2, the particle size of the base material powder is 53-106 μm; the particle size of the boron-free activator powder is 5-106 μm; when preparing the base material powder slab, the amount of binder added is 0.5%-0.8% of the base material powder; when preparing the boron-free activator slurry, the amount of binder added is 0.8%-1.2% of the boron-free activator powder; when preparing the composite slab, the mass ratio of the base material powder to the boron-free activator is 1:0.5-1.3, and the natural drying time is 8-24 hours; the vacuum pre-firing conditions are: the vacuum degree is 1.0×10 -3 Pa, heat up to 1140℃±5℃-1180℃±5℃ at a rate of 5℃-15℃ / min, and keep warm for 5min-30min.
8. The method according to claim 6, characterized in that Step 6: In the repair step, the vacuum heat treatment conditions are: vacuum degree 1.0×10 -3 Pa, heat up to 1190℃±5℃-1220℃±5℃ at a rate of 5℃-15℃ / min, and keep warm for 30min-120min.
9. A boron-free prefabricated welding plate prepared by the method described in 7 or 8.
Citation Information
Patent Citations
Brazing repair method for failures of aeroengine cobalt-based superalloy parts
CN106493506A
Compound repair method and repair material for high-temperature alloy
CN109848638A
Build-up welding material for continuous casting roll and roll using it
JP2005144488A